Indirect immunofluorescence staining patterns and their use for diagnosing cutaneous leishmaniasis and Chagas’ disease - Vásquez Huerta, Luis (2011)
Objective: To determine the value of indirect immunofluorescence (IFI) in the diagnosis of leishmaniasis and Chagas disease. Material and method: Indirect immunofluorescence (IFI) was employed for diagnosing leishmaniasis and Chagas disease using Trypanosoma cruzi epimastigota as substrate antigens. A nuclear fluorescence pattern was found in sera from patients with leishmaniasis, and a peripheral pattern was found in those with Chagas disease. Afterwards, we estimated the diagnostic value of IFI for both diseases in a blinded fashion. Results: For diagnosing leishmaniasis, IFI sensitivity was 84.2%, specificity, 100%, positive predictive value, 100%, negative predictive value 82.9%, and accuracy was 91.0%. Conclusions: The immunofluorescence technique using Trypanosoma cruzi epimastigota, considering the proposed color patterns, is useful for diagnosing cutaneous leishmaniasis and T. cruzi infection by avoiding confusion because of immune cross-reactivity between these conditions.